Household behaviour in times of political change: Evidence from Egypt - Yvonne Giesing; Almedina Music (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Using representative household survey data, we study the short-term microeconomic effects of the Egyptian revolution on household behaviour in terms of education, health expenditure and savings. We construct a new measure of political instability by analysing the number of fatalities during political protests throughout the country. Difference-in-Differences estimations show that affected households increased spending on education, especially on their sons' higher education. This can be explained by a positive outlook towards the future, with better labour market prospects. At the same time, households decreased spending on health and increased savings, which can be interpreted as precautionary behaviour.
Keywords: D14; D74; I10; I22; 330; Egypt; education; health; household savings; political uncertainty